Hallucinations and illusions a study of the fallacies of perception - Parish, Edmund (Cambridge library collection. Spiritualism and esoteric knowledge, 2011)
The psychologist Edmund Parish makes a valuable contribution to the study of the psychology of perception as well as introducing a theory of insanity in this 1897 work. The author tells the reader that it grew out of an examination of the German 'International Census of Waking Hallucinations in the Sane', the results of which he had analysed. Rather than merely translating the German original, Parish has added new information and considered criticism of his own previous work. The book is a sustained effort to define 'the common organic principle which, under whatever diversity of conditions, underlies alike normal and fallacious perception', by incorporating the most recent psychological and neurological research. Parish is especially interested in casting light on the waking hallucinations of healthy persons, as he regards this phenomenon as having been largely ignored by previous research